2016
DOI: 10.1093/molbev/msw062
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Frequency of Horizontal Gene Transfer Using Phylogenetic Models of Gene Gain and Loss

Abstract: We analyze patterns of gene presence and absence in a maximum likelihood framework with rate parameters for gene gain and loss. Standard methods allow independent gains and losses in different parts of a tree. While losses of the same gene are likely to be frequent, multiple gains need to be considered carefully. A gene gain could occur by horizontal transfer or by origin of a gene within the lineage being studied. If a gene is gained more than once, then at least one of these gains must be a horizontal transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…These plots include a Multidimensional scaling (MDS) projection of pairwise Mash distances, interactive bar charts to investigate contamination, as well as gene and contig counts. In addition we have included post processing scripts for estimating gene gain and loss rates using both the infinitely many genes (IMG) model (37,48) and the finitely many genes (FMG) model of (8,48). These are preferable to the common practice of plotting accumulation curves to indicate pangenome size as they account for the diversity and timescale of the sampled isolates.…”
Section: Structural Variationmentioning
confidence: 99%
“…These plots include a Multidimensional scaling (MDS) projection of pairwise Mash distances, interactive bar charts to investigate contamination, as well as gene and contig counts. In addition we have included post processing scripts for estimating gene gain and loss rates using both the infinitely many genes (IMG) model (37,48) and the finitely many genes (FMG) model of (8,48). These are preferable to the common practice of plotting accumulation curves to indicate pangenome size as they account for the diversity and timescale of the sampled isolates.…”
Section: Structural Variationmentioning
confidence: 99%
“…Individual gain and loss events are associated with branches based on this ancestral reconstruction. The gain and loss rates are optimized such that the likelihood for the observed presence/absence pattern of genes is maximized [32,33]. We found that optimal loss rates are always larger than the gain rates but their ratio is variable among species with a median ratio of 22 (inter-quartile range 9 to 35).…”
Section: Phylogenetic Analysis Of Gene Clustersmentioning
confidence: 91%
“…In general, systematic models of gene (or domain) gain-and-loss estimate significantly lower frequencies of HT(Zamani-Dahaj et al 2016), compared to HT estimates based on overall similarities(Nelson-Sathi et al 2015;Roettger et al 2009). HT estimates are consistently lower across the ToL: within Rickettsia, a genus(Murray et al 2016); within Cyanobacteria, a phylum and within Archaea(Zamani-Dahaj et al 2016). In addition, and importantly, these studies show that the tree-like pattern of inheritance of genomic loci is explained largely by the variation in rates of loss among lineages, and that the fraction of loci that are prone to HT is a minority…”
mentioning
confidence: 99%
“…Most potential HT events inferred from anomalous placements of gene-OTUs are associated with systematic error, even among closelyManuscript to be reviewed of genomic loci by HT. Estimation of gains is better suited for methods that are designed to systematically model gains and losses in genomes(Klopfstein et al 2015;Zamani-Dahaj et al 2016). In general, systematic models of gene (or domain) gain-and-loss estimate significantly lower frequencies of HT(Zamani-Dahaj et al 2016), compared to HT estimates based on overall similarities(Nelson-Sathi et al 2015;Roettger et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation